2016
DOI: 10.1523/eneuro.0085-15.2016
|View full text |Cite
|
Sign up to set email alerts
|

Neuron Morphology Influences Axon Initial Segment Plasticity

Abstract: Visual Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
83
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(91 citation statements)
references
References 44 publications
8
83
0
Order By: Relevance
“…Rather than reducing intrinsic excitability, our modeling predicts that shifting the AIS alone distally would weakly promote axonal firing (Fig. 5), consistent with theoretical and modeling results (9,11). Furthermore, our results indicate that, in cortical pyramidal cells, the anatomical location of the AIS is to a large degree covarying with the local somatodendritic membrane area, ensuring the generation of uniform somatic APs in the face of highly variable dendritic loads.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Rather than reducing intrinsic excitability, our modeling predicts that shifting the AIS alone distally would weakly promote axonal firing (Fig. 5), consistent with theoretical and modeling results (9,11). Furthermore, our results indicate that, in cortical pyramidal cells, the anatomical location of the AIS is to a large degree covarying with the local somatodendritic membrane area, ensuring the generation of uniform somatic APs in the face of highly variable dendritic loads.…”
Section: Discussionsupporting
confidence: 85%
“…Experimental studies showed that an activity-dependent distal shift of the AIS is associated with decreased AP output (5). In contrast, model simulations showed that shifting the AIS distally promotes excitability (9). One of the critical factors influencing AIS excitability is the large somatodendritic membrane area acting as current sink for sodium current generated in the AIS (10)(11)(12).…”
mentioning
confidence: 99%
“…Thus, a negative correlation between the AIS length and distance from the soma can maximize excitability, and this relationship is critically influenced by the conductances at both the AIS and the somato-dendritic compartments. The importance of somato-dendritic compartments to this relationship is also reported in models with realistic neuronal morphologies (Gulledge and Bravo, 2016). …”
Section: Structural Effects On Excitabilitysupporting
confidence: 53%
“…Regardless of the mechanism employed, both of these structural forms of AIS plasticity appear to serve a homeostatic purpose, bringing the cell's excitation levels closer to the state before the manipulation. It is important to note, however, that the effect of changes in AIS position on excitability are likely to depend on the cell type or model used [60]. A study of L5 cortical neurons showed that AP initiation occurred in the distal portion of the AIS, as this was sufficiently distant from the large conductive and capacitive load of the soma and dendrites [55].…”
Section: The Aismentioning
confidence: 99%
“…However, myelination is strongly variable [62] and many cell types, including hippocampal pyramidal cells in culture, have largely unmyelinated axons and much smaller cell bodies. This could possibly explain why in some cases the dissipation of current along the axonal membrane outweighs the uncoupling from the somatodendritic current sink [60], such that a distal shift of the AIS can decrease excitability instead [52]. In any case, this strongly argues for an important contribution of structural parameters such as axon diameter, soma size, and, of course, AIS length and location to neuronal output generation.…”
Section: The Aismentioning
confidence: 99%